An Enigmatic Group of Natufian Basaltic Artefacts at the Dar al-Saraya Archaeological Museum in Irbid, Jordan - Edwards, Phillip C.; Dalgamoni, Mohammed; al-Shoubaki, Sereen (Jordan Journal for History and Archaeology, 2025)
A unique group of clandestinely excavated basaltic artefacts, housed in the Dar al-Saraya Archaeological Museum in Irbid, Jordan, provides important new evidence about the Natufian period in the country. The group consists of the largest Natufian basaltic mortar ever found in Jordan, accompanied by two similarly large pestles. All that is known about the pieces is that they derive from a clandestine excavation conducted somewhere in the northern Jordan Valley, within the jurisdiction of the Irbid Governate. Footed-base mortars of the type in the Dar al-Saraya are only found in large Early Natufian village sites located in the Mediterranean region of the southern Levant. The style of the footed mortar and the two pestles, and the composition of the group as a whole, indicate that the pieces may have been looted from the early Natufian site, Wadi Hammeh 27. The stylistic resemblances are close, and Wadi Hammeh 27 is the only Natufian site in Jordan to supply any such parallels. However, if the artefacts were not from this site, there may be another large Natufian village site, somewhere in northern Jordan, that awaits discovery.